Neuropsychiatric profile of paediatric hypothalamic hamartoma: systematic review and case series. (11th April 2019) - Corbet Burcher, Georgina; Liang, Holan; Lancaster, Rebecca; Cross, J Helen; Tisdall, Martin; Varadkar, Sophia; Spoudeas, Helen A; Caredda, Elisabetta; Bennett, Sophie; Heyman, Isobel
Abstract : Aim: To evaluate neuropsychiatric comorbidities in children and adolescents with hypothalamic hamartoma. Method: We retrospectively analysed case notes for all individuals with hypothalamic hamartoma referred to Great Ormond Street Hospital, London, between 2000 and 2016. In addition, a systematic review aiming to identify all previous paediatric case series was performed. Psychiatric symptoms, demographics, physical comorbidities, and cognitive functioning were recorded for all cases where possible. Analyses were performed to determine which factors were associated with psychopathology and potential mechanisms investigated. Results: Forty‐six cases were included in the case series (28 males, 18 females; mean age at assessment 11y 8mo [1y 11mo–16y 11mo, SD 4y 0mo]). Twenty‐nine papers representing data from 264 cases met inclusion criteria for the systematic review. Overall, at least 50% of cases presented with psychopathology. Epilepsy, intellectual disability, and male sex were associated with externalizing disorders (attention‐deficit/hyperactivity disorder, conduct and oppositional defiance disorders, and rage attacks). Intellectual disability mediated the effects of epilepsy on externalizing psychopathology. No factors were associated with internalizing disorders (anxiety and depressive disorders), although these were not well reported. Interpretation: Psychiatric comorbidities are highly prevalent in the presentation of paediatric hypothalamic hamartoma. The aetiology of psychopathology comprises a range of interacting biological and psychosocial factors with particular influence from epilepsy. Further research is required to achieve an evidence base for treatment. What this paper adds: Over half of children with hypothalamic hamartoma present with psychiatric comorbidity. Externalizing and internalizing disorders are present in approximately 60% and 30% of children with hypothalamic hamartomas respectively. Epilepsy and male sex are associated with externalizing psychopathology. Intellectual disability mediates the association between epilepsy and externalizing symptoms. No clear associations are evident for internalizing disorders or precocious puberty. What this paper adds: Over half of children with hypothalamic hamartoma present with psychiatric comorbidity. Externalizing and internalizing disorders are present in approximately 60% and 30% of children with hypothalamic hamartomas respectively. Epilepsy and male sex are associated with externalizing psychopathology. Intellectual disability mediates the association between epilepsy and externalizing symptoms. No clear associations are evident for internalizing disorders or precocious puberty. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Perfil neuropsiquiátrico del hamartoma hipotalámico en pediatría: revisión sistemática y serie de casos: Objetivo: Evaluar las comorbilidades neuropsiquiátricas en niños y adolescentes con hamartoma hipotalámico. Método: En este estudio analizamos retrospectivamente las notas de los casos de todos los individuos con hamartoma hipotalámicos referidos al Great Ormond Street Hospital, London, entre el 2000 y 2016. Además, realizamos una revisión bibliográfica sistemática dirigida a identificar la serie de casos pediátricos. Síntomas psiquiátricos, demográfico, comorbilidades físicas y funcionamiento cognitivo fueron recolectados en todos los casos posibles.Se efectuaron análisis para determinar qué factores se asociaron con psicopatología y se investigaron mecanismos potenciales. Resultados: En total 46 casos fueron incluidos en la serie de casos (28 masculinos, 18 femeninos, media de edad a la evaluación 11 años y 8 meses, DS 4 años y 0 mes). La revisión bibliográfica identifico 29 artículos describiendo 264 casos que reunieron criterios de inclusión para la extracción de datos. En total, al menos 50% de casos presentaban psicopatología. Epilepsia, discapacidad intelectual, y sexo masculino fueron asociados con desórdenes externos (déficit de atención con hiperactividad, desórdenes conductuales y oposicional desafiante, ataques de furia). Ningún factor fue asociado con la internalización de desórdenes neuropsiquiátricos (desórdenes de ansiedad y depresión), aunque éstos no fueron bien reportados. Interpretación: Las comorbilidades psiquiátricas son altamente prevalentes en la presentación del hamartoma hipotalámico pediátrico. La etiología de la psicopatología comprende un rango de interacciones biológicas y factores psicosociales con particular influencia de la epilepsia. Se requiere más información de investigación para reunir evidencia científica que guie el tratamiento. Resumo: Perfil neuropsiquiátrico do hamartoma hipotalâmico pediátrico: revisão sistemática e série de casos: Objetivo: Avaliar comorbidades neuropsiquiátricas em crianças e adolescentes com hamartoma hipotalâmico. Método: Nós analisamos retrospectivamente os registros de casos de todos os indivíduos encaminhados para o Hospital Great Ormond Street, Londres, entre 2000 e 2016. Além disso, uma revisão sistemática visando identificar todos os casos pediátricos prévios foi realizada. Sintomas psiquiátricos, dados demográficos, comorbidades físicas, e funcionamento cognitivo foram registrados para todos os casos em que foi possível. Análises foram realizadas para determinar quais fatores se associavam com psicopatologia e potenciais mecanismos foram investigados. Resultados: Quarenta e seis casos foram incluídos na série de casos (28 do sexo masculino, 18 do sexo feminino; média de idade na avaliação 11a 8m (1a 11m–16a 11m, DP 4a 0m). Vinte e nove artigos representando dados de 264 casos atenderam aos critérios de inclusão para a revisão sistemática. No total, pelo menos 50% dos casos apresentaram psicopatologia. Epilepsia, deficiência intelectual, e sexo masculino eram associados com desordens externalizantes (transtorno de déficit de atenção e hiperatividade, transtornos de conduta e de desafio oposicional, e ataques de raiva). A deficiência intelectual mediou os efeitos da epilepsia e da psicopatologia externalizante. Nenhum fator foi associado com transtornos internalizantes (ansiedade e transtornos depressivos), embora estes não tenham sido bem reportados. Interpretação: Comorbidades psiquiátricas são altamente prevalentes na apresentação do hamartoma hipotalâmico pediátrico. A etiologia da psicopatologia envolve uma variedade de fatores biológicos e psicossociais que interagem, com particular influência da epilepsia. Mais pesquisas são necessárias para se atingir uma base de evidências para o tratamento.